A COMPLEX DYNAMIC EMOTIONS AND WILLINGNESS TO COMMUNICATE IN THE TASK-BASED CLASSROOM INSTRUCTIONS - Eka Fadilah; Hesty Kumala Dewi; J. Priyanto Widodo (STKIP PGRI SIDOARJO, 2022)
This study aimed to investigate the complex dynamic emotions underlying learners’ Willingness to Communicate (WtC) in the classroom interaction. Utilizing Dornyei’s (2014) Retrodictive Qualitative Modeling (RQM), we embarked with some steps: identifying learners’ archetypes, highlighting the dynamic patterns of emotions interacting to other components, and setting up signature dynamics. Eighteen participants studying English participated in two task-based instructions. Of eighteen learners of English department, we took five participants relying on their salient archetypes. We utilized K-means cluster analysis to group the learners’ archetypes that was computed by SPSS 20. Additionally, in-depth interview was carried out on the elected participants to get a thick description of the emotional states and other components underpinning L2 WtC. The results reveal twofold: (1) the participants’ dynamic patterns of emotions interacting with the classroom environment explicate the variability and fluctuation of learners’ WtC, (2) the variety of signature dynamics provided fine-grained components underlying learners’ WtC. Furthermore, the implication for further study and pedagogy is elucidated later. Key words: complex dynamic systems, emotions, Willingness to Communicate, Retrodictive Qualitative Modeling